Hell Dog - Nolan, James (Ars Medica, 2020)
When I come to, I’m relieved not to find a breathing tube jammed down my throat, although the surgeon warned there might be one. Through a morphine fog, I glance around at the peeling pea-green paint of my room in the Intensive Care Unit (ICU), a fluorescent light wincing overhead. My body has turned into a giant squid, its myriad tentacles connected to a bank of beeping machines with flickering red lights.